MEMBANGUN KESADARAN HUKUM TENTANG KEKERASAN SEKSUAL BERBASIS GENDER BAGI SISWA-SISWI DI SMP PGRI RUTAH - Wadjo, Hadibah Zachra; Salamor, Anna Maria (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
The urgency of recognizing early childhood sexual violence, including students in the world of education, aims to prevent and protect cases of sexual violence, both in the personal realm and the public realm that make children victims of sexual violence. community service program activities are carried out by providing socialization about sexual violence as well as socializing Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. After that, it was continued with a question and answer session from the participants, and the formation of agents of change among PGRI Rutah Junior High School students. After being agreed upon with the school leadership, on the appointed day, the team and students came to the PKM location. The activity was divided into 2 sessions, first, an introduction to violence, sexual violence, and the scope of sexual violence to PGRI Rutah Junior High School students. Second, a question and answer session as an interaction between participants and instructors. The activities carried out were very interesting for the students of SMP PGRI Rutah. The enthusiasm of these students was shown in the form of various questions about the material presented by the service team. This activity also collaborates with the Intra-School Student Organization (OSIS) which inaugurates 35 students as agents of change, prevention and recognition of sexual violence both in the